Sul carteggio Roversi-Fortini (1957-1993) - Vuozzo, Alessandro (L’ospite ingrato, 2024)
The study offers a general survey of the unpublished correspondence between Roberto Roversi and Franco Fortini, preserved partly in the Archivio Franco Fortini of the University of Siena and partly in the private archive of Antonio Bagnoli in Bologna. Through a selection of letters, the central themes and episodes of the epistolary exchange are explored, from the common participation in the editorial board of «Officina» to the political tensions that led in the late 1970s to the definitive break between the two intellectuals. The analysis of the documents is accompanied by an essential reconstruction of the cultural context in which the dialogue between two of the protagonists of the literary and critical-militant history of the second half of the 20th century was developed.